Effect of aqueous and alcohol extracts of Phytolacca tetramera (Phytolaccaceae) leaves on Colletotrichum gloeosporioides (Ascomycota) - Hernández, Marcelo Paulo (2013)
Phytolacca tetramera Hauman “ombusillo” is an endemism of southeastern Buenos Aires province (Argentina). This species has fungicidal action against opportunistic pathogens of humans. In order to search natural alternatives for the control of diseases in plants caused by fungi, the objective was to evaluate the effects of aqueous and alcohol extracts of P. tetramera leaves on Colletotrichum gloeosporioides (Penz.) Sacc. This fungus has a wide distribution in different species with agricultural, forestry, and ornamental value. The antifungal activity of aqueous and ethanol leaf extracts was assessed in vitro against fungi. The fungus was subjected to two types of extracts already incorporated into the Potato Dextrose Agar (PDA) medium at 5-50% concentrations. The aqueous extract concentrations within the range 15-30% led to a decrease in the average diameter and speed of mycelium growth, while the range of 15-40% was the most effective in relation to a decrease in conidial production. Also, leaf alcohol extract inhibited the conidial production at concentrations of 5%, and had fungicidal action at concentrations of 15%. From “ombusillo” leaves a foam index of 250 was obtained. This high concentration of saponins would be at least one cause of the antifungal activity.